2001
DOI: 10.5367/000000001101293788
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Sustainable Production and Genetic Resource Conservation of Bambara Groundnut: A Survey of Indigenous Agricultural Knowledge Systems

Abstract: Bambara groundnut (Vigna subterranea) is so important in most of Africa, and potentially so in other tropical regions, that improvement of its production — especially on a commercial scale — and of its germplasm both deserve renewed and intensive scientific study. Yet, compared with other legumes (such as groundnuts, beans and cowpeas), bambara groundnut has received almost no research or extension attention, although in Ghana and other parts of Africa, it has a higher market value (on a per unit weight basis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 6 publications
0
31
0
1
Order By: Relevance
“…Adu-Dapaah and Sangwan (2004) reported that the seed is regarded as a completely balanced food because it is rich in iron (4.9-48 mg/100 g), compared to (2.0-10.0 mg/100 g) for most food legumes, potassium (1144-1935 mg/100 g), sodium (2.9-12.0 mg/100 g), calcium (95.8-99 mg/100 g), protein (18.0-24.0%) with high lysine and methionine contents, ash (3.0-5.0%), fat (5.0-7.0%), fiber (5.0-12.0%), carbohydrate (51-70%), oil (6-12%) and energy (367-414 kal 100 mgG 1 ). Adu-Dapaah and Sangwan (2004), Amarteifio et al (2002), Anchirinah et al (2001) and Lackroix et al (2003) have been shown that, the energy value of bambara groundnut seed is greater than that of several other pulses. Bambara groundnuts can be eaten in many ways, immature pods can be boiled and consumed as snacks.…”
Section: Introductionmentioning
confidence: 98%
“…Adu-Dapaah and Sangwan (2004) reported that the seed is regarded as a completely balanced food because it is rich in iron (4.9-48 mg/100 g), compared to (2.0-10.0 mg/100 g) for most food legumes, potassium (1144-1935 mg/100 g), sodium (2.9-12.0 mg/100 g), calcium (95.8-99 mg/100 g), protein (18.0-24.0%) with high lysine and methionine contents, ash (3.0-5.0%), fat (5.0-7.0%), fiber (5.0-12.0%), carbohydrate (51-70%), oil (6-12%) and energy (367-414 kal 100 mgG 1 ). Adu-Dapaah and Sangwan (2004), Amarteifio et al (2002), Anchirinah et al (2001) and Lackroix et al (2003) have been shown that, the energy value of bambara groundnut seed is greater than that of several other pulses. Bambara groundnuts can be eaten in many ways, immature pods can be boiled and consumed as snacks.…”
Section: Introductionmentioning
confidence: 98%
“…It has a crisp and nutty flavor. (Anchirinah et al 2001) Bambara groundnut is eaten in several ways and at different stages of maturation. The young fresh seeds may be boiled and eaten as a snack in a manner similar to boiled peanuts and Bambara groundnut could be made into pudding locally called Moi Moi or Okpa (bean porridge) in some parts of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the obtained seed yields are low because the production environment is characterized by various abiotic and biotic stresses. Neither improved varieties nor agronomic recommendation exist, so farmers are still cultivating the local landraces (Anchirinah et al 2001, Ntundu et al 2006. Although bambara groundnut has a reputation of being more drought resistant than other legumes (Ntundu 1997), the mechanisms underlying adaptation to drought are still poorly understood (Collinson et al 1997).…”
Section: Introductionmentioning
confidence: 99%